High-temperature-resistant high-boron-silicon glass electromagnetic oven screen printing ink and preparation method thereof
Patent Information
- Application Number
- CN202611283960.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-08-24
AI Technical Summary
无机玻璃釉料需要较高温度烧结,工艺能耗较高,并可能影响已完成加工的玻璃面板;有机树脂油墨可在较低温度下固化,但普通丙烯酸、环氧或者常规有机硅油墨在电磁炉面板反复升温和冷却过程中,容易因树脂固化收缩、膜层与玻璃之间的热变形不一致以及填料-树脂界面应力集中而出现微裂纹、边缘翘起或者附着力逐渐下降
[0022]与现有技术相比,本发明提供了一种耐高温高硼硅玻璃电磁炉丝印油墨及其制备方法,具备以下有益效果:通过在聚硅氧烷网络中引入受控量的Si-O-B结构,提高成膜网络在反复受热条件下的结构稳定性。通过先使用部分硼改性聚硅氧烷树脂对熔融石英-堇青石复合填料进行预包覆,使填料颗粒与连续成膜相之间形成组成逐渐过渡的界面,减少填料边缘的局部应力集中。熔融石英和堇青石的复配既降低膜层的整体热变形,又避免单一刚性低膨胀填料大量接触形成应力传递通路。
Smart Images

Figure CN122790469B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of screen printing ink technology for glass surfaces, specifically to a high-temperature resistant high borosilicate glass induction cooker screen printing ink and its preparation method. Background Technology
[0002] High borosilicate glass has a low coefficient of linear expansion and good resistance to temperature changes, making it suitable for glass panels in household appliances that require repeated heating. To create a shielding layer, decorative patterns, or functional markings on the glass panel, an ink film is typically formed on the back of the glass using screen printing.
[0003] Existing glass screen printing materials can be broadly classified into inorganic glass enamels and organic resin inks. Inorganic glass enamels require high-temperature sintering, resulting in high energy consumption and potentially affecting the already processed glass panels. Organic resin inks can cure at lower temperatures, but ordinary acrylic, epoxy, or conventional silicone inks are prone to microcracks, edge lifting, or a gradual decrease in adhesion during repeated heating and cooling processes on induction cooker panels due to resin curing shrinkage, inconsistent thermal deformation between the film layer and the glass, and stress concentration at the filler-resin interface.
[0004] Polysiloxane backbones possess high bond energy and good heat resistance, but simply increasing the degree of crosslinking of polysiloxanes can make the film brittle; adding only low-expansion inorganic fillers can easily lead to filler agglomeration, insufficient interfacial wetting, and localized resin depletion. If there is a lack of a stable transition interface between the inorganic filler and the continuous film-forming resin, the stress generated by temperature cycling can still easily concentrate at the filler edge or the glass-film interface.
[0005] Therefore, the practical technical problem that needs to be solved is: how to reduce the interfacial stress concentration of the polysiloxane screen printing film layer during repeated heating and cooling of high borosilicate glass while maintaining screen printability and medium-temperature curing conditions, thereby inhibiting cracking, edge curling and adhesion decay. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention provides a high-temperature resistant high borosilicate glass induction cooker screen printing ink and its preparation method. By utilizing the gradient interface formed by the controlled Si-OB polysiloxane network, fused silica-cordierite low-expansion composite filler, and partially resin-pre-coated filler, the problem of screen printing film layer easily cracking and reduced adhesion under repeated temperature changes is solved.
[0007] To achieve the above objectives, the present invention provides the following technical solution: The screen printing ink comprises the following components by weight, and the sum of the weight parts of each component is 100 parts: The composition includes 28-36 parts boron-modified polysiloxane resin, 34-42 parts low-expansion composite filler, 10-16 parts heat-resistant inorganic pigment, 12-20 parts organic solvent, 0.6-1.5 parts alkoxysilane coupling agent, 0.4-1.2 parts thixotropic agent, 0.2-0.8 parts dispersant, and 0.1-0.4 parts defoamer.
[0008] Unless otherwise stated, the mass fraction of the boron-modified polysiloxane resin refers to the mass of a resin solution with a solid content of 60% to 75%, not the oven-dry mass of the resin.
[0009] Preferably, the boron-modified polysiloxane resin contains Si-OB structural units in its molecular network, the molar ratio of boron to silicon is 0.02 to 0.06, and the residual silanol content is 1.0% to 3.5% (based on the mass of the oven-dry resin).
[0010] Preferably, the low-expansion composite filler is composed of fused silica and cordierite. The mass ratio of fused silica to cordierite is preferably 2.5:1 to 4.5:1.
[0011] Preferably, 20% to 45% of the total amount of the boron-modified polysiloxane resin is distributed as a coating phase on the surface of the low-expansion composite filler particles, and the remaining resin is distributed as a continuous film-forming phase in the screen printing ink.
[0012] Preferably, the boron-modified polysiloxane resin is formed by the co-hydrolysis and condensation of methyltriethoxysilane, phenyltrimethoxysilane, dimethyldiethoxysilane, tetraethyl orthosilicate and triisopropyl borate.
[0013] Based on the total molar amount of methyltriethoxysilane, phenyltrimethoxysilane, dimethyldiethoxysilane and tetraethyl orthosilicate being 100%, preferably methyltriethoxysilane accounts for 30% to 40%, phenyltrimethoxysilane accounts for 30% to 40%, dimethyldiethoxysilane accounts for 10% to 20%, and tetraethyl orthosilicate accounts for 10% to 20%.
[0014] Preferably, the boron-modified polysiloxane resin has a weight-average molecular weight of 3,000 to 10,000, a solid content of 60% to 75%, and a molar ratio of phenyl to silicon atoms of 0.20 to 0.40. The boron element in the boron-modified polysiloxane resin exists at least partially in a -Si-OBO-Si- structure that connects two or three siloxane segments.
[0015] Preferably, the mass ratio of fused silica to cordierite in the low-expansion composite filler is 2.5:1 to 4.5:1; The median particle size D50 of the fused silica and cordierite is 0.6–2.5 μm, the particle size D90 of the low-expansion composite filler is no greater than 6 μm, and the average linear expansion coefficient of the low-expansion composite filler in the temperature range of 25–300°C is no greater than [missing value]. .
[0016] Preferably, the alkoxysilane coupling agent is 3-glycidyl etheroxypropyltrimethoxysilane; The thixotropic agent is hydrophobic fumed silica, and the dispersant is a polyether-modified polysiloxane dispersant. The organic solvent includes propylene glycol methyl ether acetate and diethylene glycol butyl ether acetate, with a mass ratio of 1:1 to 3:1. The heat-resistant inorganic pigment is selected from one or more of the following: manganese iron black spinel pigment, copper chromium manganese black spinel pigment, cobalt blue pigment, and titanium dioxide.
[0017] The present invention also provides a method for preparing the above-mentioned screen printing ink, comprising the following steps: S1. Hydrolyze and condense a siloxane precursor containing methyl, phenyl and hydroxyl groups, and introduce boron ester during the condensation process so that boron elements are connected to the polysiloxane molecular network through Si-OB structural units to obtain boron-modified polysiloxane resin. S2. Take 20% to 45% of the total mass of the boron-modified polysiloxane resin solution in the ink formulation, mix it with low-expansion composite filler, alkoxysilane coupling agent and some organic solvent, and under heating and shearing, allow the boron-modified polysiloxane resin to adsorb and coat the surface of the low-expansion composite filler particles to obtain a pre-coated filler slurry. S3. Add the remaining boron-modified polysiloxane resin, heat-resistant inorganic pigment, thixotropic agent, dispersant, defoamer and remaining organic solvent to the pre-coated filler slurry, and obtain the high-temperature resistant high borosilicate glass induction cooker screen printing ink by dispersing and grinding.
[0018] Preferably, step S1 includes: adding methyltriethoxysilane, phenyltrimethoxysilane, dimethyldiethoxysilane and tetraethyl orthosilicate to an alcohol solvent, adjusting the pH of the reaction system to 3.5-5.0 with acid, adding water and performing partial hydrolysis at 25-40°C; After hydrolysis, at least some of the free water and low-boiling alcohols are removed under heating, reduced pressure and / or inert gas purging conditions, so that the water content of the system is reduced to a predetermined range. Triisopropyl borate was diluted with anhydrous alcohol solvent and slowly added dropwise to the partially hydrolyzed siloxane system at 70–90°C to cause it to co-condense with silanol groups. After the addition is complete, the temperature is raised to 100-125°C to continue polycondensation and remove water and alcohol byproducts until the residual silanol content of the obtained resin is 1.0%-3.5%.
[0019] Preferably, in step S2, fused silica and cordierite are first mixed in a mass ratio of 2.5:1 to 4.5:1, and then alkoxysilane coupling agent, 20% to 45% of the total amount of the boron-modified polysiloxane resin and organic solvent are added. Shear dispersion for 20–45 min at 50–80℃ and 1200–2000 r / min, followed by aging at 60–85℃ for 1–3 h, so that a continuous or discontinuous boron-modified polysiloxane resin coating layer is formed on the surface of the low-expansion composite filler particles.
[0020] Preferably, in step S3, the remaining boron-modified polysiloxane resin, heat-resistant inorganic pigment and dispersant are first added to the pre-coated filler slurry and dispersed at 800-1500 r / min for 15-30 min, and then the thixotropic agent and defoamer are added and mixed. The resulting mixture is ground to a fineness of no more than 8 μm using a three-roll mill or basket mill, and then adjusted with an organic solvent to allow the resulting screen printing ink to be heated at 25°C and a shear rate of [missing information]. The viscosity under the given conditions is 60–120 Pa·s.
[0021] Preferably, the process further includes printing the prepared screen printing ink onto the non-cooking contact surface of the borosilicate glass induction cooker panel, which has been degreased and cleaned, to form a wet film with a thickness of 12–25 μm. The wet film is pre-baked at 90–120°C for 5–15 min, and then cured at 230–280°C for 20–40 min, so that the residual silanol groups of the boron-modified polysiloxane resin, the alkoxysilane coupling agent and the hydroxyl groups on the surface of the high borosilicate glass condense, and the pre-coated low-expansion composite filler is dispersed in the cured film layer.
[0022] Compared with existing technologies, this invention provides a high-temperature resistant high borosilicate glass induction cooker screen printing ink and its preparation method, which has the following beneficial effects: By introducing a controlled amount of Si-OB structure into the polysiloxane network, the structural stability of the film-forming network under repeated heating conditions is improved. By pre-coating the fused silica-cordierite composite filler with partially boron-modified polysiloxane resin, a gradually transitioning interface is formed between the filler particles and the continuous film-forming phase, reducing local stress concentration at the filler edges. The combination of fused silica and cordierite reduces the overall thermal deformation of the film layer and avoids the formation of stress transmission pathways through extensive contact of a single rigid low-expansion filler.
[0023] The aforementioned Si-OB polysiloxane network, low-expansion composite filler, and pre-coated interface are not simply used in parallel, but rather work together to address the stress formation, transmission, and release processes generated by temperature cycling, thereby improving the adhesion retention of the film layer after repeated heating and cooling and inhibiting the formation of microcracks. Attached Figure Description
[0024] Figure 1 This is a cross-sectional scanning electron microscope image of the interface between the cured film layer and the borosilicate glass in Example 3.
[0025] Figure 2 This is a scanning electron microscope image of the surface of the cured film layer in Example 3 after 100 temperature cycles. Detailed Implementation
[0026] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0027] Please see Figure 1 and Figure 2 This invention provides a technical solution for a high-temperature resistant high borosilicate glass induction cooker screen printing ink and its preparation method: Figure 1 The borosilicate glass sample screen-printed and cured in Example 3 was cut perpendicularly to the film surface. After low-shrinkage cold mounting, progressive polishing, vacuum drying, and conductive coating, cross-sectional observation was performed using a field emission scanning electron microscope at an accelerating voltage of 5 kV, a working distance of approximately 10 mm, and secondary electron imaging mode. In the figure, A represents the borosilicate glass substrate, B represents the interface between the borosilicate glass and the cured film, C represents the cured film formed by the ink in Example 3, D represents the low-expansion composite filler particles dispersed in the cured film, the double-headed arrow H represents the cross-sectional thickness of the cured film, and the scale bar represents the actual dimensions of the structure in the figure.
[0028] Figure 2The borosilicate glass samples screen-printed and cured in Example 3 were subjected to 100 temperature cycles between 25±3℃ and 300±5℃, with each temperature stage held for 30 min and the transition time between the two temperature zones not exceeding 3 min. After the cycles were completed, the samples were placed at 23±2℃ for at least 2 h, and after conductive coating, the surface was observed using a field emission scanning electron microscope at an accelerating voltage of 5 kV, a working distance of approximately 10 mm, and a secondary electron imaging mode. In the figure, A represents the surface area of the cured film layer that remains continuous after temperature cycling, B represents the granular protrusions or filler-rich morphology area on the film layer surface, C represents the boundary between the granular area and the surrounding continuous film phase, the arrows are used to indicate the actual observed continuous areas, pores, or microcracks, and the scale bar indicates the actual size of the structure in the figure.
[0029] Unless otherwise specified, the thixotropic agent, dispersant, and defoamer used in Examples 1-6 and each comparative example are the same. The thixotropic agent is a hydrophobic fumed silica surface-treated with organosilicon, specifically a hydrophobic fumed silica surface-treated with dimethyldichlorosilane, with a BET specific surface area of 90-130 m² / g. The dispersant is a polyether-modified polysiloxane dispersant, whose main active ingredient is a polysiloxane copolymer containing polyether side chains, with an active ingredient content of not less than 90% by mass. The defoamer is an organosilicon defoamer, whose main active ingredient is polysiloxane, specifically a polydimethylsiloxane defoamer.
[0030] B / Si molar ratio: After microwave digestion of the resin sample, the boron and silicon contents were determined by inductively coupled plasma atomic emission spectrometry and then converted into a molar ratio.
[0031] Weight-average molecular weight: determined by gel permeation chromatography with tetrahydrofuran as the mobile phase and calibrated with polystyrene standard samples.
[0032] Residual silanol content: After removing the solvent from the resin sample under conditions that do not induce further condensation, the hydroxyl value was determined using an acetylation-back titration method. Since no additional hydroxyl-containing organic monomers are introduced into the resin, the measured hydroxyl value was converted into Si-OH mass content.
[0033] In the formula, H represents the hydroxyl value, with units of mg KOH / g.
[0034] Particle size: The particle size of fused silica, cordierite and their composite fillers was determined by laser diffraction according to GB / T 19077-2024.
[0035] Average linear expansion coefficient of composite filler: The average linear expansion coefficients of fused silica and cordierite raw materials in the range of 25 to 300℃ were determined according to GB / T 16535-2008, and the weighted average linear expansion coefficient of composite filler was calculated according to the mass fraction of the two materials.
[0036] Pre-coated resin ratio: The pre-coated resin ratio refers to the percentage of the mass of the boron-modified polysiloxane resin solution added in step S2 to the total mass of the resin solution in the ink.
[0037] The purity of methyltriethoxysilane, phenyltrimethoxysilane, dimethyldiethoxysilane, tetraethyl orthosilicate, and triisopropyl borate is not less than 98%.
[0038] Fused quartz and cordierite were dried at 120°C for 2 hours before use and then cooled in a desiccator for later use.
[0039] The high borosilicate glass samples used in each embodiment came from the same batch and had dimensions of 100mm × 100mm × 4mm.
[0040] General preparation method of boron-modified polysiloxane resin Taking the total amount of silicon in the silane precursor as 1 mol, methyltriethoxysilane, phenyltrimethoxysilane, dimethyldiethoxysilane and tetraethyl orthosilicate were weighed according to the proportions shown in Table 1 and added to a reactor equipped with a stirrer, thermometer, dropping funnel and condenser.
[0041] Add anhydrous ethanol equivalent to 30%–50% of the total mass of the silane precursor, and then add an acidic hydrolysis solution composed of deionized water and acetic acid under stirring. The molar ratio of water to alkoxy groups in the silane precursor and the hydrolysis conditions are shown in Table 1.
[0042] After hydrolysis, triisopropyl borate is added dropwise over 30–90 minutes. The amount of triisopropyl borate added is calculated based on the target B / Si molar ratio. After the addition is complete, the temperature is raised for polycondensation, and water and alcohol byproducts are gradually removed. Once the target weight-average molecular weight and residual silanol content are reached, the temperature is lowered to below 80°C, and propylene glycol methyl ether acetate is added to adjust the solid content.
[0043] The resulting resin solution should be uniform and transparent or slightly opalescent, and should not contain any visible gel particles.
[0044] Table 1. Composition and preparation parameters of resins R1 to R6 Methyltriethoxysilane / mol% 30 40 35 45 32 38 Phenylacetyltrimethoxysilane / mol% 40 30 35 20 38 32 Dimethyldiethoxysilane / mol% 20 10 15 20 12 18 Tetraethyl orthosilicate / mol% 10 20 15 15 18 12 B / Si molar ratio 0.02 0.06 0.04 0.03 0.035 0.05 Hydrolysis pH 3.5 5 4.2 4 4.5 4.8 Water / alkoxy molar ratio 0.75 1.1 0.92 0.85 1 1.05 Hydrolysis temperature / ℃ 25 40 32 30 35 38 Hydrolysis time / h 1 3 2 1.5 2.5 2.5 Boronate ester dropping time / min 30 90 60 45 70 80 Polycondensation temperature / °C 100 125 112 108 118 122 weight average molecular weight 3000 10000 6500 5000 5500 8000 Solid mass content / % 60 75 68 65 67 72 Residual Si-OH mass content / % 3.5 1 2.2 2.8 2.5 1.5 Phenyl / Si molar ratio 0.4 0.3 0.35 0.2 0.38 0.32 The amount of triisopropyl borate added is measured according to the target B / Si molar ratio. 0.02 0.06 0.04 0.03 0.035 0.05
[0045] R1, R2, and R3 cover the lower, upper, and middle regions of the B / Si molar ratio, weight-average molecular weight, solids content, and residual silanol content, respectively. R4 is used to support the embodiment with a phenyl / Si molar ratio of 0.20.
[0046] General preparation method of screen printing ink Weigh each component according to Table 2.
[0047] First, fused silica and cordierite are mixed, then 3-glycidyl etheroxypropyltrimethoxysilane, a boron-modified polysiloxane resin solution in a predetermined proportion, and an organic solvent accounting for about 30% to 50% of the total organic solvent are added, and the mixture is sheared and dispersed at the temperatures and rotation speeds shown in Table 3.
[0048] After shearing, the material is kept at a constant temperature and aged to allow the resin and coupling agent to be adsorbed onto the surface of the filler particles, thus obtaining a pre-coated filler slurry.
[0049] Add the remaining resin, heat-resistant inorganic pigment, and dispersant to the pre-coated filler slurry for pre-dispersion; then add the thixotropic agent and defoamer, and continue mixing. Grind to the specified fineness using a three-roll mill, and add the remaining organic solvent to adjust the viscosity.
[0050] Table 2. Ink composition of Examples 1-6, unit: parts by mass Types of resins R1 R2 R3 R4 R5 R6 Boron-modified polysiloxane resin 28 36 32 28 32 32 Low expansion composite packing 42 34 38 34 38 38 Heat-resistant inorganic pigments 16 10 13 15.3 13 12 organic solvents 12 17.1 14.45 20 15.4 14.4 Coupling agent 0.6 1.5 1 1 0.9 1.2 thixotropic agents 0.8 0.6 0.8 0.8 0.4 1.2 dispersant 0.4 0.5 0.5 0.6 0.2 0.8 Defoamer 0.2 0.3 0.25 0.3 0.1 0.4 total 100 100 100 100 100 100
[0051] Examples 1-3 used manganese iron black spinel pigment; Example 4 used copper chromium manganese black spinel pigment; Example 5 used cobalt blue pigment; Example 6 used rutile titanium dioxide.
[0052] In Examples 1-6, the mass ratios of propylene glycol methyl ether acetate to diethylene glycol butyl ether acetate were 1:1, 3:1, 2:1, 1.5:1, 2.5:1, and 2:1, respectively.
[0053] Table 3. Filler, pre-coating, dispersion, and curing parameters for Examples 1-6 Fused Quartz: Cordierite 2.5∶1 4.5∶1 3.5∶1 3.0∶1 4.0∶1 3.2∶1 Fused Quartz D50 / μm 0.6 2.5 1.5 1 1.8 2 Cordierite D50 / μm 0.6 2.5 1.5 1.2 1.6 2 Composite packing D90 / μm 3 6 4.2 3.5 5 5.5 Weighted linear expansion coefficient / 10^-6K^-1 2.3 1.7 1.9 2.1 1.8 2 Pre-coated resin ratio / % 20 45 32 25 38 35 Pre-coating temperature / ℃ 50 80 65 60 70 75 Shearing speed / r·min^-1 1200 2000 1600 1400 1800 1900 Shearing time / min 20 45 32 25 35 40 Aging temperature / ℃ 60 85 72 65 75 80 Aging time / h 1 3 2 1.5 2.5 2.5 Subsequent dispersion speed / r·min^-1 800 1500 1100 1000 1200 1350 Subsequent dispersion time / min 15 30 22 20 25 28 Ink fineness / μm 8 6 6.5 7 6 5.5 Viscosity at 25℃ and 10s^-1 (Pa·s) 60 120 90 75 100 110 Printed wet film thickness / μm 12 25 18 15 20 22 Pre-drying temperature / ℃ 90 120 105 100 110 115 Pre-baking time / min 5 15 10 8 12 14 Curing temperature / ℃ 230 280 255 245 265 275 Curing time / min 20 40 30 25 35 38
[0054] Example 1: Boron-modified polysiloxane resin was prepared according to the raw material ratio and process conditions of R1 in Table 1. The components were weighed according to the formulation of Example 1 in Table 2.
[0055] Fused quartz and cordierite with a D50 of 0.6 μm were mixed at a ratio of 2.5:1, and R1, coupling agent and some solvent were added, accounting for 20% of the total resin. The mixture was sheared at 50℃ and 1200 r / min for 20 min and aged at 60℃ for 1 h.
[0056] Add the remaining R1, manganese iron black spinel pigment, dispersant, thixotropic agent, defoamer, and remaining solvent to complete dispersion and grinding. The resulting ink has a viscosity of 60 Pa·s and a fineness of 8 μm at 25℃ and 10 s⁻¹.
[0057] The ink was screen-printed onto the back of a cleaned borosilicate glass, with the wet film thickness controlled at 12 μm. It was then pre-baked at 90°C for 5 min and cured at 230°C for 20 min.
[0058] Example 2: Resin was prepared according to the raw material ratio and process conditions of R2 in Table 1. Except for the parameters listed in Tables 2 and 3, the preparation process was the same as in Example 1.
[0059] In this embodiment, R2, comprising 45% of the total resin and in a fused silica to cordierite mass ratio of 4.5:1, was used for pre-coating. The resulting ink had a viscosity of 120 Pa·s and a wet film thickness of 25 μm. After pre-baking at 120°C for 15 min, it was cured at 280°C for 40 min.
[0060] Example 3: Resin was prepared according to the raw material ratio of R3 in Table 1. The molar ratio of silane precursor was 35:35:15:15, the molar ratio of B / Si was 0.04, the weight-average molecular weight was 6500, and the residual silanol content was 2.2%.
[0061] Fused quartz and cordierite were mixed at a ratio of 3.5:1, and R3, accounting for 32% of the total resin, was used for pre-coating. The mixture was sheared at 65°C and 1600 r / min for 32 min, and then aged at 72°C for 2 h.
[0062] The resulting ink had a viscosity of 90 Pa·s and a fineness of 6.5 μm. It was printed to form an 18 μm wet film, pre-baked at 105 °C for 10 min, and then cured at 255 °C for 30 min.
[0063] Example 4: This example uses resin R4. The phenyl / Si molar ratio of R4 is 0.20.
[0064] The ink uses copper chromium manganese black spinel pigment, with 20 parts of organic solvent. The remaining composition and process parameters are shown in Tables 2 and 3.
[0065] Example 5: In this example, resin R5 and cobalt blue pigment were used. Thixotropic agent, dispersant and defoamer were taken at the lower end of the range of 0.4 parts, 0.2 parts and 0.1 parts respectively. Other parameters are shown in Table 2 and Table 3.
[0066] Example 6: In this example, resin R6 and rutile titanium dioxide were used. Thixotropic agent, dispersant and defoamer were taken at the upper end of the range of 1.2 parts, 0.8 parts and 0.4 parts respectively. Other parameters are shown in Table 2 and Table 3.
[0067] Comparative Example 1 differs from Example 3 in that triisopropyl borate is not added during resin preparation, and the B / Si molar ratio is 0. By adjusting the polycondensation time, the weight-average molecular weight, solids content, and residual silanol content of the resin are made to be basically the same as those of R3, while the rest are the same as in Example 3.
[0068] The difference between Comparative Example 2 and Example 3 is that the B / Si molar ratio was adjusted to 0.01, while the rest was the same as Example 3.
[0069] The difference between Comparative Example 3 and Example 3 is that the B / Si molar ratio was adjusted to 0.08, while the rest was the same as Example 3.
[0070] Compared with Example 3, Comparative Example 4 differs in that the proportion of pre-coated resin is adjusted from 32% to 10%, while the total amount of resin added remains unchanged. The rest is the same as in Example 3.
[0071] Compared with Example 3, Comparative Example 5 differs in that the proportion of pre-coated resin is adjusted from 32% to 55%, while the total amount of resin added remains unchanged. The rest is the same as Example 3.
[0072] Comparative Example 6 differs from Example 3 in that all cordierite was replaced with fused silica of the same mass and similar particle size, the total amount of low-expansion filler was kept at 38 parts, and the rest was the same as in Example 3.
[0073] Comparative Example 7 differs from Example 3 in that all fused quartz was replaced with cordierite of the same mass and similar particle size, the total amount of low-expansion filler was kept at 38 parts, and the rest was the same as in Example 3.
[0074] Comparative Example 8 used boron-free polysiloxane resin, and the proportion of pre-coated resin was set to 10%.
[0075] Comparative Example 8 and Example 3 constitute the following two-factor cross-validation matrix: Table 4 Comparative Example 8 0 10% Comparative Example 1 0 32% Comparative Example 4 0.04 10% Example 3 0.04 32%
[0076] In this matrix, the only difference between Comparative Example 8 and Comparative Example 1 is the pre-coating ratio; the only difference between Comparative Example 8 and Comparative Example 4 is whether or not boron is introduced; the only difference between Comparative Example 1 and Example 3 is whether or not boron is introduced; and the only difference between Comparative Example 4 and Example 3 is the pre-coating ratio.
[0077] Performance test Sample preparation The high borosilicate glass sample was cleaned sequentially with a neutral cleaning agent, deionized water, and isopropanol, and then dried at 80°C for 20 minutes.
[0078] The same 250-mesh polyester screen was used for printing. At least five parallel samples were prepared for each example and comparative example. After curing, the samples were placed in an environment of 23±2℃ and 50±5% relative humidity for 24 hours.
[0079] Temperature cycling and adhesion retention test The test followed the conversion method of temperature change test in GB / T 2423.22-2012, and combined with the usage temperature of the ink on the back of the induction cooker glass, the following settings were made: low temperature stage 25±3℃; high temperature stage 300±5℃; each temperature stage was held for 30 minutes; the conversion time between the two temperature zones of the sample did not exceed 3 minutes; one high temperature stage and one low temperature stage constituted one cycle; a total of 100 cycles were performed.
[0080] After the cycle is completed, place it in an environment of 23±2℃ for 2 hours.
[0081] Cross-cut adhesion tests were conducted according to GB / T 9286-2021. Since the cured film thickness was less than 60 μm, 1 mm spacing cross-cut blades were used. The worst adhesion rating among the five samples in each group was used as the reporting rating.
[0082] Simultaneously, vertical photographs are taken of the gridded areas, and image analysis software is used to calculate the percentage of the total gridded area where no detachment has occurred, which is recorded as the grid integrity area retention rate.
[0083] Crack area ratio Five fixed regions were selected from each sample after temperature cycling and photographed using a 50x optical microscope. The crack regions were binarized using the same threshold, and the percentage of the crack pixel area to the total field of view was calculated. The average value of all fields of view was reported for each group.
[0084] This indicator does not replace the adhesion rating in GB / T 9286-2021, but is used to quantitatively represent the degree of microcracks in the film layer after temperature cycling.
[0085] Table 5 Test Data Example 1 0 1 96 0.8 Example 2 0 1 95 1 Example 3 0 0 99 0.2 Example 4 0 1 94 1.3 Example 5 0 1 96 0.9 Example 6 0 1 95 1.1 Comparative Example 1 0 3 75 12 Comparative Example 2 0 2 86 6.2 Comparative Example 3 1 3 78 10.5 Comparative Example 4 0 3 78 11 Comparative Example 5 1 2 87 5.8 Comparative Example 6 0 2 89 4.5 Comparative Example 7 0 3 84 6.9 Comparative Example 8 0 4 60 20
[0086] As shown in Table 5, Examples 1 and 2 maintained Grade 1 cross-cut adhesion after 100 temperature cycles, with a crack area ratio not exceeding 1.0%. Example 3, after temperature cycling, had a grade 0 cross-cut adhesion and the lowest crack area ratio, indicating that the defined range is not limited to a single optimal point. Comparative Example 1 did not contain boron, and all other conditions were consistent with Example 3. The cross-cut integrity area retention rate of Comparative Example 1 after cycling decreased from 99% in Example 3 to 75%, while the crack area ratio increased from 0.2% to 12.0%, indicating that introducing a controlled amount of Si-OB structure into the polysiloxane network is beneficial for maintaining the integrity of the film layer after repeated heating. The B / Si molar ratio of Comparative Example 2 was 0.01, and the improvement effect was significantly weaker than that of Example 3. After the B / Si molar ratio of Comparative Example 3 was increased to 0.08, both the initial adhesion and the cracks after cycling deteriorated, indicating that the increased network rigidity and brittleness caused by excessive boron content could no longer bring beneficial effects, thus supporting a B / Si molar ratio range of 0.02 to 0.06. Comparative Example 4, with the pre-coated resin ratio reduced to 10%, failed to form a sufficient transition interface on the filler surface; Comparative Example 5, with the pre-coated resin ratio increased to 55%, resulted in insufficient resin distribution in the continuous film phase. Both examples exhibited lower temperature cycling performance than Example 3, supporting the limitation of a pre-coated resin ratio of 20%–45%. Comparative Example 6, using only fused silica, while suppressing overall thermal expansion of the film, enhanced rigid particle contact and localized stress transmission; Comparative Example 7, using only cordierite, showed insufficient control over overall thermal deformation. Both examples were inferior to Example 3, which combined fused silica and cordierite, demonstrating that the effects of composite fillers cannot be completely replaced by any single filler.
[0087] Depend on Figure 1 As can be seen, after curing, the ink of Example 3 forms a continuous film on the borosilicate glass surface. The low-expansion composite filler inside the film is generally evenly dispersed, and the glass-film interface is continuous. No obvious long-distance delamination or cracks penetrating the film were observed. This cross-sectional morphology indicates that the ink of Example 3, after the pre-baking and curing process, can form a relatively complete bonding interface on the borosilicate glass surface.
[0088] Depend on Figure 2 As can be seen, after 100 temperature cycles within the temperature range of 25–300°C, the surface of the cured film layer in Example 3 remained generally continuous. No obvious annular separation cracks were observed between the granular areas and the surrounding film-forming phase, and no large-area peeling or through cracks were observed within the observed field of view. These results indicate that the film layer in Example 3 still possesses good surface structural integrity after repeated temperature changes. After 100 temperature cycles, the cured film layer in Example 3 remained generally continuous, with a small number of isolated micropores or short microcracks present locally, but no large-scale interconnected cracks, obvious blistering, or flaking were observed.
[0089] Using Comparative Example 8 as the baseline, where both factors are unfavorable: The pre-coating ratio was increased from 10% to 32%, that is, from 8 comparative examples to 1 comparative example, and the integrity retention rate of the grid area was increased from 60% to 75%, an increase of 15 percentage points; By introducing a boron-modified structure with a B / Si ratio of 0.04, i.e. changing Comparative Example 8 to Comparative Example 4, the integrity area retention rate increased from 60% to 78%, an increase of 18 percentage points.
[0090] Based on a simple addition estimate, the complete area retention rate when both are used simultaneously should be approximately: 60% + 15% + 18% = 93%. The result of Example 3 was 99%, which was 6 percentage points higher than the prediction of simple addition.
[0091] For crack area ratio: Comparative sample 8 was 20.0%; After increasing the pre-coating ratio, the ratio of 1 decreased to 12.0%, a reduction of 8.0 percentage points on its own; After introducing the boron-modified structure, the content of Comparative Example 4 decreased to 11.0%, a reduction of 9.0 percentage points on its own.
[0092] A simple summation predicts that the crack area ratio after using both methods simultaneously is approximately: 20.0% − 8.0% − 9.0% = 3.0%. It can be seen that the Si-OB network improves the heat resistance structure retention of the continuous film phase, and the pre-coated composite filler reduces the stress concentration at the filler-resin interface. When both exist simultaneously, the resin network and the filler interface no longer independently bear the thermal cycling stress, but form a continuous stress buffer and transfer structure, thus producing a synergistic effect that exceeds the simple superposition of effects.
Claims
1. A high-temperature resistant high borosilicate glass induction cooker screen printing ink, characterized in that, The product comprises the following components by mass, and the sum of the mass parts of each component is 100 parts: The composition includes 28-36 parts boron-modified polysiloxane resin, 34-42 parts low-expansion composite filler, 10-16 parts heat-resistant inorganic pigment, 12-20 parts organic solvent, 0.6-1.5 parts alkoxysilane coupling agent, 0.4-1.2 parts thixotropic agent, 0.2-0.8 parts dispersant, and 0.1-0.4 parts defoamer. The mass fraction of the boron-modified polysiloxane resin refers to the mass of a resin solution with a solid mass content of 60% to 75%. The boron-modified polysiloxane resin has a molecular network containing Si-OB structural units, the molar ratio of boron to silicon in the boron-modified polysiloxane resin is 0.02 to 0.06, and the mass content of residual silanol groups in the resin is 1.0% to 3.5% (dry resin). The low-expansion composite filler is composed of fused silica and cordierite; 20% to 45% of the total amount of boron-modified polysiloxane resin is distributed as a coating phase on the particle surface of the low-expansion composite filler, and the remaining boron-modified polysiloxane resin is distributed as a continuous film-forming phase in the screen printing ink.
2. The high-temperature resistant borosilicate glass induction cooker screen printing ink according to claim 1, characterized in that, The boron-modified polysiloxane resin is a co-hydrolysis condensation product of methyltriethoxysilane, phenyltrimethoxysilane, dimethyldiethoxysilane, tetraethyl orthosilicate and triisopropyl borate. Based on the total molar amount of methyltriethoxysilane, phenyltrimethoxysilane, dimethyldiethoxysilane and tetraethyl orthosilicate as 100%, methyltriethoxysilane accounts for 30% to 40%, phenyltrimethoxysilane accounts for 30% to 40%, dimethyldiethoxysilane accounts for 10% to 20%, and tetraethyl orthosilicate accounts for 10% to 20%.
3. The high-temperature resistant borosilicate glass induction cooker screen printing ink according to claim 1 or 2, characterized in that, The boron-modified polysiloxane resin has a weight-average molecular weight of 3,000 to 10,000, a solid content of 60% to 75%, and a molar ratio of phenyl to silicon atoms of 0.20 to 0.
40. The boron element in the boron-modified polysiloxane resin exists at least partially in a -Si-OBO-Si- structure that connects two or three siloxane segments.
4. The high-temperature resistant borosilicate glass induction cooker screen printing ink according to claim 1, characterized in that, The mass ratio of fused silica to cordierite in the low-expansion composite filler is 2.5:1 to 4.5:1; The median particle size D50 of the fused silica and cordierite is 0.6–2.5 μm, the particle size D90 of the low-expansion composite filler is no greater than 6 μm, and the average linear expansion coefficient of the low-expansion composite filler in the temperature range of 25–300°C is no greater than [missing value]. .
5. The high-temperature resistant borosilicate glass induction cooker screen printing ink according to claim 1, characterized in that, The alkoxysilane coupling agent is 3-glycidyl etheroxypropyltrimethoxysilane; The thixotropic agent is hydrophobic fumed silica, and the dispersant is a polyether-modified polysiloxane dispersant. The organic solvent includes propylene glycol methyl ether acetate and diethylene glycol butyl ether acetate, with a mass ratio of 1:1 to 3:
1. The heat-resistant inorganic pigment is selected from one or more of the following: manganese iron black spinel pigment, copper chromium manganese black spinel pigment, cobalt blue pigment, and titanium dioxide.
6. A method for preparing the high-temperature resistant high borosilicate glass induction cooker screen printing ink according to any one of claims 1 to 5, characterized in that, Includes the following steps: S1. Hydrolyze and condense a siloxane precursor containing methyl, phenyl and hydroxyl groups, and introduce boron ester during the condensation process so that boron elements are connected to the polysiloxane molecular network through Si-OB structural units to obtain boron-modified polysiloxane resin. S2. Take 20% to 45% of the total mass of the boron-modified polysiloxane resin solution in the ink formulation, mix it with low-expansion composite filler, alkoxysilane coupling agent and some organic solvent, and under heating and shearing, allow the boron-modified polysiloxane resin to adsorb and coat the surface of the low-expansion composite filler particles to obtain a pre-coated filler slurry. S3. Add the remaining boron-modified polysiloxane resin, heat-resistant inorganic pigment, thixotropic agent, dispersant, defoamer and remaining organic solvent to the pre-coated filler slurry, and obtain the high-temperature resistant high borosilicate glass induction cooker screen printing ink by dispersing and grinding.
7. The preparation method according to claim 6, characterized in that, Step S1 includes: Methyltriethoxysilane, phenyltrimethoxysilane, dimethyldiethoxysilane and tetraethyl orthosilicate are added to an alcohol solvent, the pH of the reaction system is adjusted to 3.5-5.0 with acid, water is added and partial hydrolysis is carried out at 25-40℃; After hydrolysis, at least some of the free water and low-boiling alcohols are removed under heating, reduced pressure and / or inert gas purging conditions; Triisopropyl borate was diluted with anhydrous alcohol solvent and slowly added dropwise to the partially hydrolyzed siloxane system at 70–90°C to cause it to co-condense with silanol groups. After the addition is complete, the temperature is raised to 100-125°C to continue polycondensation and remove water and alcohol byproducts until the residual silanol content of the obtained resin is 1.0%-3.5%.
8. The preparation method according to claim 6, characterized in that, In step S2, fused silica and cordierite are first mixed in a mass ratio of 2.5:1 to 4.5:1, and then alkoxysilane coupling agent, 20% to 45% of the total amount of the boron-modified polysiloxane resin and organic solvent are added. Shear dispersion for 20–45 min at 50–80℃ and 1200–2000 r / min, followed by aging at 60–85℃ for 1–3 h, so that a continuous or discontinuous boron-modified polysiloxane resin coating layer is formed on the surface of the low-expansion composite filler particles.
9. The preparation method according to claim 6, characterized in that, In step S3, the remaining boron-modified polysiloxane resin, heat-resistant inorganic pigment and dispersant are first added to the pre-coated filler slurry and dispersed at 800-1500 r / min for 15-30 min. Then, thixotropic agent and defoamer are added and mixed. The resulting mixture is ground to a fineness of no more than 8 μm using a three-roll mill or basket mill, and then adjusted with an organic solvent to allow the resulting screen printing ink to be heated at 25°C and a shear rate of [missing information]. The viscosity under the given conditions is 60–120 Pa·s.
10. The preparation method according to any one of claims 6 to 9, characterized in that, It also includes printing the prepared screen printing ink onto the non-cooking contact surface of the high borosilicate glass induction cooker panel that has been degreased and cleaned to form a wet film with a thickness of 12 to 25 μm. The wet film is pre-baked at 90–120°C for 5–15 min, and then cured at 230–280°C for 20–40 min, so that the residual silanol groups of the boron-modified polysiloxane resin, the alkoxysilane coupling agent and the hydroxyl groups on the surface of the high borosilicate glass condense, and the pre-coated low-expansion composite filler is dispersed in the cured film layer.
Citation Information
Patent Citations
Composite colored particle for inkjet ink, process for producing it, predispersion for inkjet ink and inkjet ink
JP2004155979A
Thermally conductive sheet
US20170198188A1
